AN ANALYSIS OF ENGLISH-INDONESIAN TRANSLATION PROCEDURES USED IN INSTAGRAM MOBILE APPLICATION - Putri Eka Sujianti; Merilyn Simbolon; Maria Arina Luardini (Postgraduate School, Universitas Nusa Cendana, 2020)
This research is intended to identify the English-Indonesian translation procedures used in Instagram mobile application and to find outthe most dominant procedure used in translating words and phrases in Instagram mobile application from English to Indonesian version. The theoryof translation procedures used in this research was proposed by Vinay and Darbelnet. By applying qualitative method,it is intended to investigate aphenomenon on Instagram mobile application and the discussion was presented descriptively. To ensure the trustworthiness of the research, the datawere deeply observed by reading both English and Indonesian version. The findings show that there are five out of seven procedures are applied intranslating words and phrases in Instagram mobile application from English to Indonesian version. Those are (1) literal translation with theoccurrence of 42 out of 86 or 48.8%, (2) borrowing with the occurrence of 22 out of 86 or 25.6%, (3) transposition with the occurrence of 19 out of86 or 22.1%, (4) adaptation with the occurrence of 2 out of 86 or 2.3%, (5) equivalence with the occurrence of 1 out of 86 or 1.2%. The mostdominant translation procedure used in Instagram mobile application from English to Indonesian version is literal translation. Meanwhile, there wereno data found being translated from English to Indonesian using calque and modulation.